Canavalia ensiformis beans as an unconventional alternative for intensive lamb fattening - Luna-Palomera, Carlos (2025)
The aim of this study was to evaluate the productive performance and benefit-cost ratio (B:C) of fattening lambs in confinement with diets that included Canavalia ensiformis beans in meal (CH) or pelleted (CP). Twelve Pelibuey lambs with an initial live weight of 15.0 ± 0.64 kg were used, randomly assigned to treatments that included CH or CP at levels of 25% (25CH and 25CP) and 50% (50CH and 50CP) as a protein source. Final live weight (FW), daily weight gain (DWG), daily feed intake (DFI), feed conversion ratio (FCR), usable feed efficiency (UFE), and benefit : cost ratio (BCR) were evaluated during the initiation and development stages. In the first period, the variables FW, DFI, FCR, and UFE were similar (p>0.05) between treatments. Control lambs had the highest DWG (270.6 g/d). In the development period, lambs in the Control and 50CH groups had the best FCR and lowest UFE (p<0.05), while lambs in the 25CH, 25CP, and 50CP groups had the lowest FCR and highest UFE. The best BCR (US$1.20) was for lambs in the 50CP group, with a profitability of 16.75%. It is concluded that the inclusion of Canavalia ensiformis beans in meal (25%) or pellets (50%) is an unconventional protein source that can be used in lamb fattening, with acceptable production performance and profitability.